2017
DOI: 10.36722/sst.v3i4.235
|View full text |Cite
|
Sign up to set email alerts
|

Keanekaragaman Fitoplankton Sungai Ciliwung Pasca Kegiatan Bersih Ciliwung

Abstract: <p><em>Abstrak </em>- <strong>Sungai Ciliwung merupakan salah satu sungai yang tercemar karena banyak dimanfaatkan oleh warga jakarta diantaranya untuk kegiatan industri dan rumah tangga. Salah satu parameter biologi yang dapat digunakan sebagai indikator perubahan lingkungan yaitu Fitoplankton. Peran fitoplankton dalam ekosistem perairan yaitu sebagai produsen primer, hal ini karena fitoplankton memiliki kemampuan untuk fotosintesis. Penelitian ini dilaksanakan pada bulan Februari samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
1
1
1
4
Order By: Relevance
“…According to Effendi et al [49], numerous factors can obscure quantitative inferences from eDNA water samples, causing practical is the most common phylum found in the Lower Ciliwung River. These findings corroborate Pambudi et al [46], who observed that the group of phytoplankton that dominates freshwaters consists primarily of Bacillariophyta (diatoms) due to their high adaptability to the environment and rapid reproduction. According to Sirait et al [50], dominance of Bacillariophyta shows competition in resource utilisation and unbalanced or stressed aquatic environmental conditions.…”
Section: Eukaryotic Phytoplankton and Zooplankton Compositionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to Effendi et al [49], numerous factors can obscure quantitative inferences from eDNA water samples, causing practical is the most common phylum found in the Lower Ciliwung River. These findings corroborate Pambudi et al [46], who observed that the group of phytoplankton that dominates freshwaters consists primarily of Bacillariophyta (diatoms) due to their high adaptability to the environment and rapid reproduction. According to Sirait et al [50], dominance of Bacillariophyta shows competition in resource utilisation and unbalanced or stressed aquatic environmental conditions.…”
Section: Eukaryotic Phytoplankton and Zooplankton Compositionsupporting
confidence: 91%
“…However, this study detected more phytoplankton phyla (Bacillariophyta, Chlorophyta, Cryptista, Haptophyta, Ochrophyta, and Miozoa) than the 5 phytoplankton phyla (Bacillariophyta, Chlorophyta, Charophyta, Ochrophyta (former Chrysophyta), Cyanobacteria (former Cyanophyta), and Rhodophyta) reported by Pambudi et al [46]. This study did not detect Cyanobacteria as found by Pambudi et al [46]. This is thought to be caused by the primer used, namely the universal primer for metazoans.…”
Section: Eukaryotic Phytoplankton and Zooplankton Compositioncontrasting
confidence: 80%
“…Bacillariophyta has high adaptability to aquatic conditions and can reproduce quickly [21]. Diatom, a kind of autotrophic photosynthetic eukaryotic algae, is an essential primary producer.…”
Section: Biodiversity Assessmentmentioning
confidence: 99%
“…Selain itu, kategori tingkat kesuburan rendah (oligotrofik) pada Stasiun 2 dan 3 di musim penghujan karena memiliki nilai kecepatan arus paling tinggi dari stasiun yang lain sehingga memungkinkan fitoplankton terbawa arus perairan. Pambudi et al (2017) menyatakan selain kurang dapat beradaptasi dengan kondisi lingkungan, rendahnya kelimpahan fitoplankton juga dipengaruhi oleh kecepatan arus. Kecepatan arus yang tinggi berakibat pada rendahnya kelimpahan fitoplankton karena kecepatan arus mempengaruhi pergerakan fitoplankton.…”
Section: Selainunclassified